O Legislativo e a política externa brasileira: o desempenho da Comissão de Relações Exteriores e de Defesa Nacional da Câmara dos Deputados e da Comissão de Relações Exteriores e Defesa Nacional do Senado Federal nos governos Luiz Inácio Lula da Silva - Herculano, Luciene Soares (2014)
This work examines the institutional role and the activities carried out by the Foreign Relations and National Defense Committee of the Brazilian Chamber of Deputies and by the Foreign Relations and National Defense Committee of the Brazilian Senate, carried out during the 52nd and 53rd legislative sessions (from February 2003 to January 2011), in the process of formulating, implementing and overseeing the guidelines that oriented brazilian foreign policy. During the period of 2003 and 2010, which comprised the two-term presidency of Luiz Inácio Lula da Silva, of the Workers Party (PT), several issues became controversial in the Brazilian foreign relations arena. Beginning with a review of the Political Science and International Relations bibliography about the behavior of the National Congress and the dynamics involved in Brazilian foreign relations, the scope of this work is focused on the activities of the two permanent legislative committees. Composed by a wide range of technical and partisan profiles, these legislative niches are formed based on the appointments made by the congressional leadership and carry out a specific role within Congress: to address the country s international agenda. This dissertation aims to go beyond the account of activities related in the Annual Reports issued by each of the houses by including analyses of the constitutional, legal, informational and political aspects. More than recounting the results of eight years of work by these two nuclei of National Congress, this work seeks to observe these committees from the partisan, ideological and electoral perspectives. The examination of all the evidence supports the conclusion that legislators have been considerably proactive, participant and influential in Brazilian foreign policy decision-making. Differently from what previous studies have indicated, despite legal, constitutional and institutional limitations, the Chamber of Deputies and the Federal Senate have not relinquished or delegated to the Executive Branch their roles in this regard. By highlighting this productivity, the current survey shows that these committees have been able to maintain, by their own activities, their autonomy in regard to external factors, such as pressure from the Executive and the aspirations of the constituency